HUBUNGAN ANTARA KEMAMPUAN KOMUNIKASI ASERTIF DENGAN KEJADIAN PERILAKU AGRESIF PADA REMAJA - Yunalia, Endang Mei; Haryuni, Sri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Aggressive behavior is an action that aims to dominate or behave destructively by using verbal or physical strength aimed at the object. Aggressive behavior can occur at any stage of age including adolescents. Emotional development in adolescence causes adolescents to have a high desire for something, where this period is a critical period and a time of rebellion. One of the factors that influence the aggressive behavior in adolescents is the ability to carry out assertive communication. The purpose of the study was to determine the relationship between assertive communication skills and aggressive behavior in adolescents. This study used descriptive correlation design with cross sectional approach. The sample of 42 was recruited using simple random sampling in SMA 5 Kota Kediri. The result showed that there most a half respondent (40,5%) have good assertive communication skills with moderate levels of aggressive behavior. Based on Chi Square: ρ-value 0,000< 0,05 it has been recognized that there is a correlation between assertive communication skills and aggressive behavior in adolescents. Based on the results of these studies it is expected that parents or the school will provide education about the importance of assertive communication and can be a role model for adolescents in behaving so that the incidence of aggressive behavior and juvenile delinquency can be reduced.